How (Not) to Sell Nuclear Weapons - Jehiel, Philippe; Moldovanu, Benny; Stacchetti, Ennio (American Economic Review, 1996)
We consider situations where a sale affects the ensuing interaction between potential buyers. These situations are modeled by assuming that an agent who does not acquire the object for sale incurs an identity-dependent externality. We construct a revenue-maximizing auction for the seller. We observe that: 1) outside options and participation constraints are endogenous. 2) The seller extracts surplus also from agents who do not obtain the auctioned object. 3) The seller is better-off by not selling at all (while obtaining some payments) if externalities are much larger than valuations.